2023
DOI: 10.6023/cjoc202206035
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on the Synthesis of Nine-Membered N-Heterocycles

Abstract: Nine-membered N-heterocycle scaffolds are widely found in natural products and biologically active molecules. The rigid structure of the medium-sized ring plays important roles in the regulation of their biological and pharmacological activities. Therefore, nine-membered N-heterocycle is one of the most attractive medium-sized ring compounds. Because of the increasing entropy and ring extension of nine-membered ring skeleton, the synthesis of nine-membered N-heterocycles is still difficult; especially the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Additionally, numerous reviews have been reported on the synthesis of medium-sized heterocycles through different strategies. [25][26][27][28][29][30][31][32] However, the abovementioned reviews lacked specific approaches for the construction of eight-membered N-heterocycles. Therefore, herein, we intend to summarize different synthetic methods involving the most representative examples and reported literature on the synthesis of eight-membered N-heterocycles in the last 20 years (1995-2023).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, numerous reviews have been reported on the synthesis of medium-sized heterocycles through different strategies. [25][26][27][28][29][30][31][32] However, the abovementioned reviews lacked specific approaches for the construction of eight-membered N-heterocycles. Therefore, herein, we intend to summarize different synthetic methods involving the most representative examples and reported literature on the synthesis of eight-membered N-heterocycles in the last 20 years (1995-2023).…”
Section: Introductionmentioning
confidence: 99%